Routledge handbook of human trafficking - Piotrowicz, Ryszard W.; Rijken, Conny; Uhl, Bärbel Heide (Routledge international handbooks, 2019)
International and regional regimes on anti-trafficking -- Genealogies of human trafficking and slavery -- Trafficking in human beings as a crime and as a human rights violation -- Trafficking in transnational criminal law -- The European legal regime on trafficking in human beings -- Trafficking in human beings in the African context -- Human trafficking in the context of labour migration in Southeast Asia : the case of thailand's fishing industry -- Human trafficking in Australasia -- Human trafficking in the Middle East -- Types of exploitation -- Defining exploitation in the context of trafficking : what is a crime and what is not -- Human trafficking for the purpose of organ removal -- Child soldiering in relation to human trafficking -- Tracing the emergence of ict-enabled human trafficking for ransom -- Exploitation through begging as a form of trafficking in human beings : over-estimated or under-reported? -- Particular legal issues -- The non-punishment provision with regard to victims of trafficking : a human rights approach -- Abuse of a position of vulnerability within the definition of trafficking in persons -- Unable to return? : the protection of victims of trafficking in need of international protection -- Prosecution of cases of human trafficking in a common law system -- Prosecution of trafficking in human beings in civil law systems : the example of belgium -- Needs of victims of trafficking -- Trafficking in persons : a victim's perspective -- Child trafficking : a call for rights-based integrated approaches -- The right to a remedy and reparation for victims of trafficking in human beings -- Being home : exploring family re-integration amongst trafficked indonesian domestic workers -- The mental health of trafficked persons -- National referral mechanisms -- Critical discourses of the anti-trafficking framework -- Sex and work : understanding sexual commerce in an era of "globalisation" -- Orwellian rights and the un trafficking protocol -- Collateral damage provoked by anti-trafficking measures -- Disrupting religious privilege : code of conduct for religious institutions, faith communities and faith-based organizations for their work with survivors of forced labour, human trafficking and modern slavery -- The interface between trafficking in persons and culture -- Statistics, data and knowledge -- Work in progress: international statistics on human trafficking -- Knowledge production on human trafficking and everyday governance practices -- Assumptions built into code : digital data, human trafficking and human rights : a troubled relationship? part vi: actors, stakeholders and institutions -- Changing the system from within : the role of ngos in the flawed anti-trafficking framework -- The role of the UN special rapporteur on trafficking in persons, especially women and children -- Trafficking in human beings and international peacekeeping -- Can labour make an effective contribution to legal strategies against human trafficking? -- Economic aspects -- Exploitation of migrant workers and trafficking in human beings : a nexus of the demand by employers, workers and consumers -- Fifteen years lifting of the ban on brothels : the struggle of policy makers between sex workers as agents or victims -- A critical engagement with the "pull and push" model: human trafficking and migration into sex work 40. of coyotes and caporali : how anti-trafficking discourses of criminality depoliticise mobility and exploitation -- Trafficking in human beings and the informal economy -- The business of trafficking in human beings